(RETRACTION) Efek Centella asiatica terhadap resistensi insulin pada parameter biokimia mencit yang diberi diet tinggi lemak - Dwita, Nounik Cheri; Arozal, Wawaimuli; Barinda, Again Jeffilano; Safutra, Sadam (Faculty of Medicine, Universitas Andalas, 2024)
Efek Centella asiatica terhadap resistensi insulin pada parameter biokimia mencit yang diberi diet tinggi lemak. 2024; 1422-1431: The above article, published online on January, 2024 in Majalah Kedokteran Andalas, https://doi.org/10.25077/mka.v46.i9.p1434-1443.2024 , has been retracted by agreement between the authors and the journal's Editor in Chief, dr. Hirowati Ali, Ph.D. The retraction has been agreed after the authors asked to retract the article due to a misattribution of authorship.